Peran Kecerdasan Buatan Untuk Perlindungan Data Nasabah Dalam Aktivitas Operasional Sektor Perbankan - Mercurius Broto Legowo; Sarongan, Fangky Antoneus; Nurani Buaty (Universitas Mandiri Bina Prestasi, 2024)
Artificial intelligence has now become one of the innovative technologies in the industrial world and its existence can support this in several areas of business operations, one of which is protecting customer data in the banking sector. However, the application of artificial intelligence in protecting customer data in operational activities in the Indonesian banking sector still faces several obstacles in its implementation. The main objective of this research is to examine the role of Artificial Intelligence in protecting customer data in banking sector operational activities. This study is descriptive research with a quantitative approach. Data collection through distributing online surveys. The research results describe the main obstacles to implementing artificial intelligence to protect customer data in banking operational activities, various uses of artificial intelligence applications, as well as their positive and negative impacts. The hope is that this research can contribute to Indonesian banking to improve its operational activities, especially in protecting customer data.